9g+6m=26

Simple and best practice solution for 9g+6m=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9g+6m=26 equation:


Simplifying
9g + 6m = 26

Solving
9g + 6m = 26

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-6m' to each side of the equation.
9g + 6m + -6m = 26 + -6m

Combine like terms: 6m + -6m = 0
9g + 0 = 26 + -6m
9g = 26 + -6m

Divide each side by '9'.
g = 2.888888889 + -0.6666666667m

Simplifying
g = 2.888888889 + -0.6666666667m

See similar equations:

| 4x-1=13x-71 | | -2=31+7 | | x^2-6= | | 3(x+1)+2x=-32 | | x+9=18+-24 | | 34+4=18 | | 34+4=8 | | 6x+34=16x-56 | | -5x-8x=-52 | | 5-(7X+3)=0 | | 23-4=5 | | 6[4(8-y)-5(9+3y)]-21=-7[3(7+4y)-4] | | 6y-2=13 | | -x^2-40x-80=0 | | -3=8(3)+9 | | 6-4(3x-1)=-26 | | 11x^2=26x-x^3 | | 1=3(3)+9 | | 3=1(3)+9 | | 7x^2-4+7x-9x^2-4x= | | 14x+4y=24 | | 6-x=2x-12 | | 47=4x-5 | | 7x+33-x=3x+39 | | =9b^2-48b+64 | | -x^2+x-4+2x+-x^2= | | 2=3(2)+9 | | 2(s-4)7=-19 | | 4-6=2x-2 | | 4p-5q=29 | | 9c-11=c+25 | | 5x+155=11x-13 |

Equations solver categories